Pelatihan Penerapan Keterampilan Dasar Mengajar Bagi Calon Guru - , (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2024)
Islamic Religious Education plays a crucial role in shaping the character of individuals and societies through religious values. At Kuantan Singingi Islamic University, special attention is given to the development of prospective Islamic Religious Education teachers. A community service program titled "Implementation of Basic Teaching Skills for Prospective Teachers" has been carried out with the aim of improving the quality of Islamic Religious Education by enhancing the teaching skills of prospective teachers. This program involves stages ranging from planning, and implementing training, to monitoring and evaluation. Consequently, there has been a significant improvement in lesson planning, the use of interactive teaching strategies, and holistic assessment by prospective teachers. Specially prepared outreach materials help students understand and apply basic teaching skills in the context of learning in the Islamic Religious Education Study Program. In addition to directly benefiting prospective teachers, this activity also enhances students' understanding of the importance of thorough preparation to become professional teachers. Furthermore, this community service program also enhances the reputation and quality of students in the Islamic Religious Education Study Program at Kuantan Singingi Islamic University, and provides inspiration for similar institutions to improve the quality of learning through mastering basic teaching skills.